2015
DOI: 10.1590/0104-1169.0024.2593
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge of the nursing staff at a teaching hospital on blood transfusion

Abstract: Objective: to determine whether there is an association between knowledge of the nursing professionals about blood transfusion and the variables related to the professional aspects. Method: this is an observational, cross-sectional and quantitative study, carried out at a large general teaching hospital. The sample consisted of 209 nursing professionals, obtained by simple random sampling. For data collection, a checklist was used. In the univariate analysis, descriptive statistics and central trend and disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 10 publications
3
18
1
5
Order By: Relevance
“…In this study, the lowest knowledge score was recorded for the "during and post-transfusion nursing responsibilities and management of adverse reactions" section (mean = 67.14%). This coincided with results of another study in which the lowest score was recorded for the "during transfusion step" (12). None of the nurses in the current study scored 100%, which agreed with previous studies conducted in the United Arab Emirates and Turkey (7,13).…”
Section: Knowledge Of During and Post-transfusion Nursing Responsibilsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the lowest knowledge score was recorded for the "during and post-transfusion nursing responsibilities and management of adverse reactions" section (mean = 67.14%). This coincided with results of another study in which the lowest score was recorded for the "during transfusion step" (12). None of the nurses in the current study scored 100%, which agreed with previous studies conducted in the United Arab Emirates and Turkey (7,13).…”
Section: Knowledge Of During and Post-transfusion Nursing Responsibilsupporting
confidence: 92%
“…The mean score (67.14%, SD = 16.71) for Section 4 was lower than that of the other sections. Eighty-three percent of subjects (n = 154, 83.3%) were able to answer at least four items correctly, and only seven of them mean knowledge score in this study was higher than that reported in other studies (7)(8)12). This could be due to the low number of knowledge items assessed in this study (22 items) compared to others (> 35 items) (7-8, 12), as fewer items increased the weight of each question on the 100% scale.…”
Section: Knowledge Of During and Post-transfusion Nursing Responsibilcontrasting
confidence: 76%
See 1 more Smart Citation
“…The three predictor variables of this study were: Trained or specific guidance for blood transfusion; Participation in specific training for blood transfusion; and Self-confidence to the procedure, which meet the discussions in the literature involving the theme (8,17). It is worth emphasizing the need to encourage the training and qualification of these professionals from the training courses (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…In addition Diakité, Diawara, and Tchogang, 2012 (20) ,who found that about half of participants had insufficient knowledge related to blood transfusion. Also this result was consistent with Kabinda, et al, 2014 ( 21 ) who clarified that because of lack of continuous and regular training in blood transfusion result in insufficient knowledge among nursing staff about principle of blood safety.…”
Section: Discussionmentioning
confidence: 99%